SINDROM METABOLIK PADA PENYAKIT PARU OBSTRUKTIF KRONIK - Yunita Arliny (Jurnal Kedokteran Syiah Kuala, 2012)
Abstrak. Penyakit paru obstruktif kronik sering dikaitkan dengan beberapa penyakit seperti penyakit jantung, osteoporosis, diabetes dan sindrom metabolik. Penyakit jantung dan kanker paru-paru adalah penyebab utama kematian pada pasien dengan COPD. Sindrom metabolik adalah kumpulan dari beberapa komponen yang terkait dengan risiko kejadian kardiovaskular dalam bentuk lingkar pinggang meningkat, tekanan darah tinggi, dislipidemia dan peningkatan kadar glukosa darah. Berat badan pada pasien dengan PPOK memberikan prognosis yang baik, tetapi di sisi lain meningkatkan risiko penyakit kardiovaskular.Abstract. Chronic obstructive pulmonary disease is often associated with several diseases such as cardiovascular disease, osteoporosis, diabetes and metabolic syndrome. Cardiovascular disease and lung cancer is the leading cause of death in patients with COPD. Metabolic syndrome is a collection of some of the components associated with the risk of Cardiovascular events in the form of increased waist circumference, elevated blood pressure, dyslipidemia, and elevated levels of blood glucose. Weight gain in patients with COPD provide a good prognosis but on the other hand increases the risk for cardiovascular disease.